1997
DOI: 10.1007/bf02737746
|View full text |Cite
|
Sign up to set email alerts
|

Role and functions of Poisons Information Centre

Abstract: The Poisons Information Centre (PIC) is a specialized unit providing information on prevention, early diagnosis and treatment of poisoning and hazard management. Most of the developed and many developing countries have well established poison control centres with poisons information service, patient management facility and analytical laboratory. In India, the National Poisons Information Centre (NPIC) was established in February, 1995 in the Department of Pharmacology at the All India Institute of Medical Scie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…It also depends on the ability to locate, analyze and deliver the information required in a skillful, efficient and evidence-based manner to meet the needs of the requestor and document enquiries and information given in a clear and systematic manner. [8121314151719] Hence, we evaluated the quality of services provided by the center.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It also depends on the ability to locate, analyze and deliver the information required in a skillful, efficient and evidence-based manner to meet the needs of the requestor and document enquiries and information given in a clear and systematic manner. [8121314151719] Hence, we evaluated the quality of services provided by the center.…”
Section: Discussionmentioning
confidence: 99%
“…[101112] For the management of poisoning cases, poison information centers are a ready source of help as they can provide authentic information and guidelines for first aid and treatment of emergencies related to toxic exposures. [1011] A global study undertaken during the period 1984-1986 indicated that while most of the developed countries had well-established facilities for poison control, this was rarely the case in developing countries.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations